Comparison of the Effect of Ethanol Extracts of Phaleria macrocarpa (scheff.Boerl) Fruit and Metformin on the Kidney Function of Hyperglycaemic Rat Models - Eman Sutrisna; Nur Signa Aini Gumilas; Mus topa; Evy Sulistyoningrum (Herb-Medicine Journal: Terbitan Berkala Ilmiah Herbal, Kedokteran dan Kesehatan, 2020)
Diabetes mellitus is a disease that often causes diabetic nephropathy complications due to persistent hyperglycaemia. Phaleria macrocarpa (scheff. Boerl)  is one of the plants that has been widely used in the treatment of diabetes mellitus, but its effect on the risk of diabetic nephropathy is still unknown. A dose of 300mg / 200gbb / day is known as an effective dose that can significantly reduce blood sugar levels in diabetic rat. The Streptozotocin Effect (STZ) causes damage to the pancreas and causes hyperglycaemia. This study aims to compare the effect of Phaleria macrocarpa (scheff. Boerl) fruit extracts on urea and creatinine levels as a parameter of kidney function in hyperglycaemic mouse models. The study was carried out experimentally using the post-test only with control group design. Fifteen white rats were divided into 3 groups. All rats were induced with 40 mg / 200gbb of Streptozotocin (STZ) to experience hyperglycaemia. Group I as negative control was given aquades. Group II was given ethanol extract of Phaleria macrocarpa (scheff. Boerl) with a dose of 300 mg / 200gbw / day. Group III was given Metformin at a dose of 150 mg / 200gbw / day. On the 22nd day of treatment, blood specimens were taken for examination of urea and creatinine levels. The research data were statistically analyzed with α <0.05; CI95%. The mean of urea levels in Group I (79.80 ± 25.09 mg / dl), II (76.00 ± 22.59 mg / dl and III (59.60 ± 6.35 mg / dl). Kruskal-Wallis test results showed no significant difference in urea levels between treatment groups (p value = 0.273; CI95%). The mean of creatinine levels in Group I (0.68 ± 0.07 mg / dl), II (0.63 ± 0.14 md / dL) and III (0.98 ± 0.25 mg / dL). One Way Anova and Post hoc test results showed a significant difference in mean creatinine levels between Groups I and III (p = 0.014; 95% CI) and II with III ( p value = 0.006; CI95%). the results of this study can be concluded that the extract of Phaleria macrocarpa (scheff. Boerl) fruit flesh at a dose of 300 mg / 200gbb has better effectiveness than metformin dose 150 mg / 200gbb in repairing the kidney function of hyperglycaemia rats.